The simulation of diurnal surface thermal contrast in sea ice and tundra terrain - Outcalt, Samuel I. (Archiv für Meteorologie, Geophysik und Bioklimatologie Serie B, 1973)
A simple surface climate simulator has the capacity to model the thermal contrast produced by stratification, variable sea ice or active layer thickness and albedo in the environment of the Alaskan North Slope. These simulations form the background for modeling the probable effects of terrain modifications produced by Arctic construction. This strategy should allow investigators to estimate the most appropriate times for the discrimination of specific targets using thermal imagery as a prospecting medium and facilitate the interpretation of existing imagery. Lastly, the scheme allows investigators of surface modification effects to select probable subsets of processes for field evaluation by examining the sensitivity of the thermal response to variations of the input properties over their anticipated ranges in conjunction with estimates of the local meteorological environment. This sequence can also be used to test the physical validity of process arguments used in the interpretation of thermal contrast in reconnaissance imagery. Ein einfaches Modell des Bodenklimas besitzt die Fähigkeit, den thermischen Kontrast, der durch Stratifikation, variable Eisbedeckung oder aktive Schichtdecke und Albedo in der Umgebung des Nordhanges Alaskas hervorgerufen wird, abzubilden. Die Modellrechnungen bilden die Basis für eine Abschätzung des Effektes von Veränderungen des Geländes im Zusammenhang mit Bauarbeiten in der Arktis. Mit diesem Modell sollte es auch möglich sein, die günstigsten Zeiten für die unterschiedliche Behandlung spezifischer Zielgebiete unter Anwendung von Temperaturabbildungen als Aufschließungsmittel ausfindig zu machen und die Interpretation der bestehenden Temperaturabbildungen zu erleichtern. Letzten Endes erlaubt das Modell, auf Grund einer Untersuchung der Empfindlichkeit der thermischen Reaktion auf Änderungen der Anfangsbedingungen in ihrem möglichen Variationsbereich im Zusammenhang mit den örtlichen meteorologischen Bedingungen die Auswahl von Teilprozessen bei der Untersuchung von Auswirkungen ...